7 skills for the future : adaptability, critical thinking, empathy, integrity, optimism, being proactive, resilience - Prince, Emma-Sue (Pearson Education, 2019)
This business book is great for leaders, middle managers, entrepreneurs and anyone interested in: personal development; soft skills for the future; resilience & adaptability. Feeling in control over your life is crucial to success and wellbeing. Our world is changing - so fast, so furiously, so ferociously - that to stand out you need to tap into your own resources and competences. Doing so puts you firmly back into the driving seat of your own life, enabling you to be happier, find and do work you love and have a true sense of purpose. But what are the key competences that you need? 7 Skills for the Future sets the scene for seven new soft skills that will propel you forward. Through a combination of scientific research, no-nonsense advice, practical exercises and case studies, this book shows you how to understand, develop and use: adaptability; critical thinking; empathy; integrity; optimism; being proactive; reslience. By learning how to tap into these essential skills, and understanding how to put them into practice each day of our lives, we can be happier, more effective and abler to cope with change in an uncertain and exciting future.